Respostas
respondido por:
1
Vamos primeiramente determinar o 5° termo.
a₁ = 2
a₂ = 6
n = 5
q = 6 / 2 = 3
a₅ = a₁ . qⁿ⁻¹
a₅ = 2 . 3⁵⁻¹
a₅ = 2 . 3⁴
a₅ = 2 . 81
a₅ = 162
Soma dos termos:
S₅ = [a₁ . (qⁿ - 1)] / q - 1
S₅ = [2 . (3⁵ - 1)] / 3 - 1
S₅ = [2 . (243 - 1)] / 2
S₅ = [2 . 242] / 2
S₅ = 484 / 2
S₅ = 242
Espero ter ajudado. Valeu!
a₁ = 2
a₂ = 6
n = 5
q = 6 / 2 = 3
a₅ = a₁ . qⁿ⁻¹
a₅ = 2 . 3⁵⁻¹
a₅ = 2 . 3⁴
a₅ = 2 . 81
a₅ = 162
Soma dos termos:
S₅ = [a₁ . (qⁿ - 1)] / q - 1
S₅ = [2 . (3⁵ - 1)] / 3 - 1
S₅ = [2 . (243 - 1)] / 2
S₅ = [2 . 242] / 2
S₅ = 484 / 2
S₅ = 242
Espero ter ajudado. Valeu!
respondido por:
0
Resposta:
Vamos primeiramente determinar o 5° termo.
a₁ = 2
a₂ = 6
n = 5
q = 6 / 2 = 3
a₅ = a₁ . qⁿ⁻¹
a₅ = 2 . 3⁵⁻¹
a₅ = 2 . 3⁴
a₅ = 2 . 81
a₅ = 162
Soma dos termos:
S₅ = [a₁ . (qⁿ - 1)] / q - 1
S₅ = [2 . (3⁵ - 1)] / 3 - 1
S₅ = [2 . (243 - 1)] / 2
S₅ = [2 . 242] / 2
S₅ = 484 / 2
S₅ = 242
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás